Functional Gastrointestinal Disorders in Mediterranean Countries According to Rome IV Criteria. Issue 3 (25th March 2022) - Strisciuglio, Caterina; Cenni, Sabrina; Serra, Maria Rosaria; Dolce, Pasquale; Kolacek, Sanja; Sila, Sara; Trivic, Ivana; Lev, Michal Rozenfeld Bar; Shamir, Raanan; Kostovski, Aco; Papadopoulou, Alexandra; Roma, Elefthería; et al.
ABSTRACT: Objectives: The aim of this study was to assess the prevalence of functional gastrointestinal disorders (FGIDs) in children of Mediterranean area using Rome IV criteria and to compare the prevalence of FGIDs using Rome IV and Rome III criteria. Methods: This was a cross-sectional study enrolling children and adolescents living in Croatia, Greece, Israel, Italy, Macedonia, and Serbia. Subjects were examined in relation to the presence of FGIDs, using the Rome IV criteria. Data were compared with the results of a previous study using Rome III data. Results: We analyzed 1972 children ages 4 to 9 years (group A), and 2450 adolescents 10 to 18 years old (group B). The overall prevalence of FGIDs was 16% in group A and 26% in group B, with statistical differences among countries in both groups ( P < 0.001). In group A, the prevalence of FGIDs and of functional constipation (FC) was significantly lower than in the previous study ( P < 0.001), whereas in group B no significant difference was found. In both groups of age, the prevalence of abdominal migraine and irritable bowel syndrome decreased significantly ( P < 0.001 and P < 0.001, respectively) using Rome IV versus Rome III criteria, conversely functional dyspepsia increased ( P < 0.001). Conclusions: FGIDs are common in children and adolescents, their frequency increases with age, and there is a significant variation in the prevalence of some FGIDs among different European countries. The application of the Rome IV criteria resulted in a significantly lower prevalence of FGIDs in children compared with Rome III criteria.